Kontrol Struktur Geologi Terhadap Pola Mineralisasi Di Desa Hulawa, Pohuwato, Provinsi Gorontalo - Diwa Ahmad Luly; Aang Panji Permana; Noviar Akase; Muhammad Kasim; Ronal Hutagalung; Agustinus Sosang (Universitas Negeri Gorontalo, 2026)
This study was conducted in Hulawa Village, Buntulia District, Pohuwato Regency, Gorontalo Province, located within the North Arm of Sulawesi, an area known for its epithermal mineralization potential. The research aims to analyze the relationship between geological structures and mineralization patterns. The methodology involved geological surface mapping, structural measurements, lineament analysis, and stereographic interpretation using Dips 7.0 and WinTensor software. Geomorphologically, the study area consists of fault-controlled mountainous and hilly terrains. The identified lithologies include Lapilli Tuff, Porphyritic Rhyodacite, Rhyodacite Breccia, Dacite, Biotite Dacite, and Diorite. Structural analysis indicates that the area was affected by a principal compressional stress (σ1) trending Northwest–Southeast (NW–SE), which generated conjugate fracture systems oriented NW–SE and Northeast–Southwest (NE–SW). These structures acted as conduits for hydrothermal fluid migration. Two dominant vein orientations were identified: NE–SW trending oxidized quartz veins in the northeastern area and NW–SE trending sulfide-rich stockwork veins containing pyrite and chalcopyrite in the southwestern area. Geochemical analysis shows that Cu, As, and Mo anomalies are spatially associated with structural zones, indicating strong structural control on hydrothermal fluid circulation and mineral deposition. Overall, mineralization in the Hulawa area is interpreted to be controlled by conjugate fracture systems and strike-slip fault structures